Triple-strand-forming methylphosphonate oligodeoxynucleotides targeted to mRNA efficiently block protein synthesis. - Reynolds, M A (1994)
Antisense oligonucleotides are ordinarily targeted to mRNA by double-stranded (Watson-Crick) base recognition but are seldom targeted by triple-stranded recognition. We report that certain all-purine methylphosphonate oligodeoxyribonucleotides (MPOs) form stable triple-stranded complexes with complementary (all-pyrimidine) RNA targets. Modified chloramphenicol acetyltransferase mRNA targets were prepared with complementary all-pyrimidine inserts (18-20 bp) located immediately 3' of the initiation codon. These modified chloramphenicol acetyltransferase mRNAs were used together with internal control (nontarget) mRNAs in a cell-free translation-arrest assay. Our data show that triple-strand-forming MPOs specifically inhibit protein synthesis in a concentration-dependent manner (> 90% at 1 microM). In addition, these MPOs specifically block reverse transcription in the region of their complementary polypyrimidine target sites.